Hunter-fisher-gatherer river transportation: Insights from sourcing the obsidian of Hasankeyf Höyük, a Pre-Pottery Neolithic A village on the Upper Tigris (SE Turkey). (10th February 2021) - Carter, Tristan; Moir, Rose; Wong, Todd; Campeau, Kathryn; Miyake, Yutaka; Maeda, Osamu
Abstract: As a means of contributing to discussions on regional diversity in the earliest Neolithic lifeways of the Fertile Crescent (10th millennium cal BC), this article presents an EDXRF-based sourcing study of 332 obsidian artifacts from the hunter-fisher-gatherer village of Hasankeyf Höyük in southeastern Anatolia. While the techno-typological choices detailed conform largely to a pre-defined Upper Tigris cultural tradition, the distinctions in raw material selection reflect the "mosaic of exploitation strategies" that have come to typify the socio-economic practices of Early Holocene communities in the larger region (southwest Asia). Five obsidian sources are represented in the analyzed sample, with Nemrut Dağ products being dominant, plus smaller amounts of Bingöl A, Bingöl B, Muş and 'Group 3d' obsidian. The preference for Nemrut Dağ obsidian distinguishes this village from others of the Upper Tigris. By using a GIS-based least cost-path analysis, we suggest that community-specific traditions of raw material choice were part-influenced by these hunter-fisher-gatherers' use of rivers as their primary means of reaching the obsidian sources. The importance of the Tigris and its tributaries for transportation and cultural interaction is supported by various proxy data that lead us to argue that riverine movement and communication was an important aspect of Early Holocene lifeways in southwest Asia that has hitherto been largely ignored by archaeologists.